2020
DOI: 10.1002/jcph.1740
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal Hormone Therapy—Local and Systemic: A Pharmacologic Perspective

Abstract: Every woman, if she lives long enough, will transition into menopause, and as the US population ages, women will be spending more time in a postmenopausal state than before. For postmenopausal women, the decision to initiate menopausal hormone therapy should be individualized. A thorough evaluation of the patient's cardiovascular, venous thromboembolic, cancer, and fracture risk should be considered along with the woman's quality of life. Hormone therapy exerts its therapeutic effects on vasomotor symptoms, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 77 publications
(189 reference statements)
0
7
0
1
Order By: Relevance
“… 9 , 10 Menopausal hormone therapy is an effective treatment for VMS and is considered to be a safe treatment option in healthy menopausal women when initiated before the age of 60 or within 10 years of menopause. 11 , 12 In addition to managing bothersome menopausal symptoms, hormone therapy (HT) effectively reduces the risk of fractures associated with menopausal bone loss and osteoporosis. 11 , 12 Multiple studies have demonstrated beneficial cardiovascular effects of timely HT use, especially in women who undergo menopause before the age of 45.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 , 10 Menopausal hormone therapy is an effective treatment for VMS and is considered to be a safe treatment option in healthy menopausal women when initiated before the age of 60 or within 10 years of menopause. 11 , 12 In addition to managing bothersome menopausal symptoms, hormone therapy (HT) effectively reduces the risk of fractures associated with menopausal bone loss and osteoporosis. 11 , 12 Multiple studies have demonstrated beneficial cardiovascular effects of timely HT use, especially in women who undergo menopause before the age of 45.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 In addition to managing bothersome menopausal symptoms, hormone therapy (HT) effectively reduces the risk of fractures associated with menopausal bone loss and osteoporosis. 11 , 12 Multiple studies have demonstrated beneficial cardiovascular effects of timely HT use, especially in women who undergo menopause before the age of 45. 13 …”
Section: Introductionmentioning
confidence: 99%
“…3,4 Menopausal hormone therapy is considered a standard treatment for bothersome vasomotor symptoms. 5 For the average healthy postmenopausal woman, hormone therapy is considered a safe and effective treatment of bothersome vasomotor symptoms when initiated within 10 years of menopause or under the age of 60 years. 4,5 In addition to quality of life benefits, menopausal hormone therapy is a recognized treatment for reducing the risk of fractures associated with osteoporosis.…”
mentioning
confidence: 99%
“…5 For the average healthy postmenopausal woman, hormone therapy is considered a safe and effective treatment of bothersome vasomotor symptoms when initiated within 10 years of menopause or under the age of 60 years. 4,5 In addition to quality of life benefits, menopausal hormone therapy is a recognized treatment for reducing the risk of fractures associated with osteoporosis. Recent publications have also addressed the cardiovascular benefits of menopausal hormone therapy, especially in women who undergo early menopause.…”
mentioning
confidence: 99%
See 1 more Smart Citation